IMPLEMENTASI MEDIA VIDEO PEMBELAJARAN BERBASIS MNEMONIC DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA - Netriwati, Netriwati; Nuryani, Puja; Fadila, Abi; Nendra, Fadly (De Fermat : Jurnal Pendidikan Matematika, 2026)
This research aims to develop a feasible and effective mnemonic-based learning video to improve students’ understanding of mathematical concepts. This research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subject of the study is a student in class X of SMA Negeri 1 Banjit. The instruments used in this study include expert validation questionnaires, student response questionnaires, and concept understanding tests through pre-tests and post-tests. The validation results showed that mnemonic-based learning videos obtained an average score of 3.79 from material experts and 3.78 from media experts with valid categories. The results of student responses in the small group and large group trials showed that the categories were very interesting. In addition, the results of the effectiveness test showed an increase in students’ understanding of concepts with an average pre-test score of 40.35 and post-test of 80.07. The result of the N-Gain analysis of 0.66 is in the medium category. Thus, the mnemonic-based learning videos developed are declared feasible and quite effective in mathematics learning to improve students’ understanding of mathematical concepts.